Discovery of a Histidine‐Based Scaffold as an Inhibitor of Gut Microbial Choline Trimethylamine‐Lyase. (10th September 2020) - Gabr, Moustafa; Świderek, Katarzyna
Abstract: Anaerobic choline metabolism by human gut microbiota to produce trimethylamine (TMA) has recently evolved as a potential therapeutic target because of its association with chronic kidney disease and increased cardiovascular risks. Limited examples of choline analogues have been reported as inhibitors of bacterial enzyme choline TMA‐lyase (CutC), a key enzyme regulating choline anaerobic metabolism. We used a new workflow to discover CutC inhibitors based on focused screening of a diversified library of small molecules for intestinal metabolic stability followed by in vitro CutC inhibitory assay. This workflow identified a histidine‐based scaffold as a CutC inhibitor with an IC50 value of 1.9±0.2 μM. Remarkably, the identified CutC inhibitor was able to reduce the production of TMA in whole‐cell assays using various bacterial strains as well as in complex gut microbiota environment. The improved efficiency of the new scaffold identified in this study in comparison to previously reported CutC inhibitors would enable optimization of potential leads for in vivo screening and clinical translation. Finally, docking studies and molecular‐dynamic simulations were used to predict putative interactions created between inhibitor and CutC. Abstract : All stop ! We have identified a novel scaffold that can inhibit trimethylamine (TMA)‐lyase expressed by human gut bacteria with an IC50 value of 1.9±0.2 μM. The reported inhibitor displayed universal inhibition of TMA lyase in multiple bacterial strains and maintained the inhibitory activity in complex biological environment.